2022
DOI: 10.1002/aelm.202200046
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Insulator Transition Driven by Traps in 2D WSe2 Field‐Effect Transistor

Abstract: trap charges. [7,10] These electrically active interface traps can adversely affect device performance by reducing charge carrier mobility, increasing subthreshold swing, and enhancing off-state current (reducing on/off ratio). [7] In addition, these charge impurities near the surface of 2D materials and different kinds of disorders can strongly suppress electronic interactions and control the electrical characteristics of the system. [11][12][13] Since the pioneering observation of metal-insulator transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 49 publications
0
17
1
Order By: Relevance
“…The n C values of different hBN encapsulated BP devices are almost similar, indicating that our results are consistent and reproducible. It should be noted that the n C in our study is lower than the previously reported n C of BP with ionic liquid gating 33 and even lower than those of MoS 2 , 17,20,22 WSe 2 , 16,24 and ReS 2 . 21 In general, n C depends on the order of disorder in the 2D system.…”
Section: ■ Introductioncontrasting
confidence: 91%
See 3 more Smart Citations
“…The n C values of different hBN encapsulated BP devices are almost similar, indicating that our results are consistent and reproducible. It should be noted that the n C in our study is lower than the previously reported n C of BP with ionic liquid gating 33 and even lower than those of MoS 2 , 17,20,22 WSe 2 , 16,24 and ReS 2 . 21 In general, n C depends on the order of disorder in the 2D system.…”
Section: ■ Introductioncontrasting
confidence: 91%
“…This has allowed us to investigate the microscopic origin of 2D MIT by excluding the role of R C on the BP channel. On the other hand, the 2D MIT has been observed in various 2D materials. However, the microscopic origin of MIT is still not clearly understood. For example, the 2D classical percolation-based transition has been used to demonstrate MIT in monolayer MoS 2 , and multilayer CuIn 7 Se 11 due to density inhomogeneities of electronic states.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The carrier densities according to each thickness were calculated using eq where q is the elementary charge. When V g = 0 and V T = −4.94, −5.45, −7.32, and −10.15 V, carrier densities were calculated as n = 3.72 × 10 11 , 4.10 × 10 11 , 5.52 × 10 11 , and 7.69 × 10 11 cm –2 , respectively.…”
Section: Resultsmentioning
confidence: 99%